Análises transcricionais no processo de adesão por Paracoccidioides brasiliensis e caracterização funcional de adesinas - NOGUEIRA, Sarah Veloso (2010)
Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis (PCM), a human systemic mycosis, prevalent in Latin America. Extracellular matrix (ECM) is a complex net where collagens, laminin and fibronectin can be found and, when exposed, is the first site for the fungus adhesion. Our aim was to study genes involved in the adhesion process using Representational Difference Analysis (RDA). RDA is a PCR-coupled subtractive method that allows the isolation of genes differentially expressed in two different cDNA populations. Hence, cDNAs were synthesized from RNAs extracted from P. brasiliensis yeast cells adhered to collagen and fibronectin to identify overexpressed genes. Genes involved in a wide range of cellular process were found and PbCtr3 (cooper transporter) and enolase (PbEno) were chosen to further studies. A synthetic peptide (PbCTR3) and the recombinant enolase (rPbEno) were utilized together with the anti-rPbEno polyclonal antibody in functional analysis with ECM components and plasminogen. The studies suggest that P. brasiliensis enolase, in the surface, is able to generate plasmin from plasminogen by plasminogen activator. Therefore, it was also demonstrated that this protein is secreted and able to promote fungus adhesion and invasion to cells. These findings clearly establish the role of enolase in the patogenicity of P. brasiliensis.